DESAIN PERANGKAT-KERAS KOMPONEN PENDUKUNG PENGEMBANGAN RADAR SEKUNDER UNTUK TRACKING TIGA DIMENSI TRAYEKTORI UJI COBA ROKET - Darjat Darjat (TEKNIK, 2010)
Topic executed by is " Development of Secondary Radar For The Tracking Of Three Dimension Trajectory Test-Drive The National Rocket".In first year of research focussed at desain and making of component of hardware of producer of radio frequency 900 MHZ. Technological Development of rocket is not quit of other technology, one of them is secondary radar. Communications of radio data overcome through the secondary radar need a component hardware capable to awaken the radio frequency as according to wanted job frequency.This article study about method of hardware desain transceiver which usually implementation by PLL ( Phase Locked Loop) or underlayer modulation locked by the phase to arrange the VCO ( Voltage Controlled Oscillator) what is used. Component used by is IC transceiver RFM12BP integrating all function of radio frequency in single chipPrototype which is being developed by to build the transceiver FSK use the unit microcontroller , crystal, capacitor and antenna; separated. Obtained by result that system of radio frequency developed by earn the implementation for the system of secondary radar ably stable frequency at specified frequency arrangement